Interpretation Catalysts in Cyberspace - Ingber, Rebecca (Texas law review, 2017)
The leaders of the Tallinn process recognized that the specific expertise necessary for the first Tallinn project on cyber warfare would not be sufficient for the broader scope of Tallinn 2.0.[...]they expanded the team and, while retaining the same leadership, brought in an almost entirely new group of legal experts with backgrounds involving not just the law of armed conflict, but also diplomatic law, the law of the sea, space law, and, as we have discussed, human rights.[...]the Manual notes that care was taken to send individual chapters out to "experts in the respective subjects" to "prepare[] initial drafts of the rules and commentary," as well as to seek peer review by experts at later points on drafts of the Manual.61 Yet in broadening the group of experts and expertise-and this is of course only conjecture-the process may have encountered increased friction the second time around in coming to consensus on even what applicable body of law to apply to a particular context, let alone the precise contours of the legal rule.While surely a group of experts in any single field will have areas of disagreement, there are also likely to be significant areas of consensus among actors within a shared field, and more so than there might be if views were instead solicited from a broader array of experts from multiple fields.[...]one can readily imagine that a group of, say, LOAC experts may find more avenues for agreement with respect to how LOAC might apply to a novel context, than would a more diverse group of experts drawn from disparate fields of expertise in seeking consensus on the applicability of rules from any given field.[...]the Tallinn Manual itself ultimately concluded both that "the law of armed conflict did not apply to those cyber operations because the situation did not rise to the level of an armed conflict," and that "there is no definitive evidence that the hacktivists involved in the cyber operations against Estonia in 2007 operated pursuant to instructions from any State, nor did any State endorse and adopt the conduct.